Exome sequencing shows same pattern of clonal tumor mutational burden, intratumor heterogenicity and clonal neoantigen between autologous tumor and Vigil product - David Willoughby; Ernest Bognar; Laura Stanbery; Casey Nagel; Gladice Wallraven; Aman Pruthi; Nicholas Bild; Ericca Stamper; Donald Rao; Adam Walter; John Nemunaitis (Scientific Reports)
Abstract Retrospective data support overall survival (OS) advantage to high clonal tumor mutation burden (cTMB), high clonal neoantigen load (cNEO) and low intratumor heterogeneity (ITH) in cancer patients who receive immunotherapy. In order to explore this relationship prospectively with Vigil, a triple function targeted immunotherapy involving ovarian cancer patients in long term follow up of the Phase 2b VITAL trial, we developed an exome sequencing procedure and associated bioinformatics pipeline to determine clonal signal patterns. DNA libraries containing exome sequences tagged with unique molecular identifiers (UMI) were prepared from paired samples and sequenced on Illumina sequencers to high coverage depths of ~ 930X (tumor) and ~ 130X (normal). Raw sequence reads were processed into optimized binary alignment map (BAM) files, using the UMI information. The BAM files were inputted into modules for calling MHC-I alleles, annotating single nucleotide variants (SNVs) and small insertions/deletions (InDels), and for determination of allelic copy number. The outputs were used to predict the sequence of peptide neoantigens and to perform clonality analysis in order to assign each SNV and InDel in a patient tumor sample to a primary clone or subclone. The Clonal Neoantigen pipeline was further assessed using whole exome Illumina sequencing data from three previously published studies. Evaluation of the pipeline using synthetic sequencing data from a sub-clonal deconvolution tool benchmarking study, showed positive predictive value (PPV) and positive percent agreement (PPA) of > 97.5% and > 96.5%, respectively, for SNV and InDel detection with minimum requirements for variant density and allele fraction. Haplotype calls from the Clonal Neoantigen pipeline MHC-I/ MHC-II typing module matched a published benchmark for 91.5% of the calls in a sample of 99 patients. Analysis of exome sequencing data from 14 patients with advanced melanoma revealed a strong correlation between cTMB values determined by the Clonal Neoantigen pipeline as compared to those calculated from the published data (R2 = 0.99). Following validation, the wet lab process and Clonal Neoantigen pipeline was applied to a set of matched normal, tumor, and Vigil product samples from 9 (n = 27 samples) ovarian cancer subjects entered into the VITAL (CL-PTL-119) trial. Results demonstrated marked correlation (R2 = 0.98) of cTMB between tumor used to construct Vigil and Vigil product. Correlation between tumor and Vigil for the cNEO and ITH metrics, showed R2 values of 0.95 and 0.87, respectively. The consistency of the Clonal Neoantigen pipeline results with previously published data as well as the agreement between results for tumor and Vigil for the entire system provide a strong basis of support for utilization of this pipeline for prospective determination of cTMB, cNEO, and ITH values in clinical tumor tissue in order to explore possible correlative relationships with clinical response parameters.